2017
DOI: 10.1021/acssuschemeng.7b00233
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Scale Algal Biomass Production Using Algal Biofilm Reactor and Conversion to Energy and Chemical Precursors by Hydropyrolysis

Abstract: A pilot-scale algal biofilm reactor (P-ABR) was assessed for its potential to provide a continuous supply of high volume algal biomass to be utilized as feedstock for hydropyrolysis. The half-year long performance assessment showed significantly high productivity of 15−20 g m −2 d −1 with uniform biochemical composition. Hydropyrolysis (HyPy) using ZSM-5 was used to convert and partition ABR-grown algal biomass components into energy-rich biocrude (HyPyO), nutrient-rich aqueous condensate (HyPyA), carbon-rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, it should be noted that too high acidity can also lead to polymerization and coke formation [15]. Several other research groups have also used H-ZSM-5 in catalytic hydropyrolysis both as a catalyst [18][19][20][21][22][23] and as support [19][20][21]24].…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that too high acidity can also lead to polymerization and coke formation [15]. Several other research groups have also used H-ZSM-5 in catalytic hydropyrolysis both as a catalyst [18][19][20][21][22][23] and as support [19][20][21]24].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have investigated catalytic hydropyrolysis using Pyroprobe reactors and H-ZSM-5, often impregnated with Ni [9][10][11][12][13][14][15]. Melligan et al [15] investigated the effect of hydrogen pressure at 600 °C using a Ni/H-ZSM-5 catalyst and found that increasing the hydrogen pressure increased the higher heating value (HHV) of the products, due to an increased degree of deoxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…This work focuses on results obtained in (semi-)continuous bench scale and pilot plant reactors. Despite that several research groups have investigated catalytic hydropyrolysis in Pyroprobe reactors [34,[47][48][49][50][51][52], these results are generally not discussed in this work due to their relatively poor comparability with results obtained from (semi-)continuous reactors.…”
Section: Introductionmentioning
confidence: 99%